The Role of Quality Time in Building Family Harmony: A Qualitative Study of Parent-Child Relationships - Rani Rahmawati; Nisrina Salsabila; Siti Nurul Azizah; Sri Damayanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Abstract Social changes and increasing work demands in modern families have led to a decrease in the intensity of interaction between parents and children, making quality time an important strategy for maintaining family harmony. This study aims to analyze the perspectives of parents and children regarding family harmony, the forms and roles of quality time in maintaining family relationships, as well as the challenges and efforts families make in dealing with disharmony. The method used is a qualitative approach with a phenomenological design. Data collection was conducted through in-depth interviews with three informants consisting of a father, a mother, and a child. Data analysis was performed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The research results indicate that family harmony is understood as a relationship filled with love, good communication, mutual respect, and emotional closeness among family members. The forms of quality time practiced by the family include eating together, going for walks, having casual conversations, and sharing stories about daily activities. Quality time plays a crucial role in strengthening emotional bonds, fostering more open interpersonal communication, and maintaining harmonious relationships between parents and children. However, this study also identified obstacles such as work demands, gadget use, and communication barriers that affect family interactions. Therefore, efforts are needed to raise families’ awareness of the importance of open communication, balanced time management, and reducing excessive gadget use so that harmony and emotional closeness within the family can be maintained. Keyword: Family Communication, Family Harmony, Parent-Child Relationships, Quality Time, Structural Functionalism.